PENGARUH PEMECAHAN MASALAH TERHADAP PENINGKATAN HASIL BELAJAR SENAM ARTISTIK - Pamuji Sukoco (Jurnal Cakrawala Pendidikan, 2011)
Abstract: The Contributions of Problem Solving on the Improvement of Artistic Gymnastics Learning Outcomes. This study aims to improve the psychomotor skills in artistic gymnastics and cognitive skills of the students of Physical Education, Health, and Recreation (PEHR), Faculty of Sports Sciences, Yogyakarta State University in the academic year of 2008/2009 through the problem-solving learning strategy. This was an action research study involving two cycles. The subjects were the students of the non-regular PEHR program. The data were analyzed using the quantitative descriptive technique. The results showed that the learning approach to artistic gymnastics using the problem-solving learning strategy was capable of improving the psychomotor and cognitive skills indicated by the artistic gymnastics learning outcomes with a mean of 7.02. Keywords: problem solving, learning outcomes, artistic gymnastics